Peran Dewan Direksi dan Kinerja Perusahaan: Environmental, Social and Governance sebagai Mediator - Adelina Citradewi (Jurnal Akuntansi dan Audit Syariah)
Based on data from the Indonesia Stock Exchange (IDX), it is known that in 2023 there were 88 companies listed in Morningstar Sustainalytics out of a total of 857 companies listed on the IDX as a whole. This is an interesting phenomenon, where only about ± 10% of listed companies on the IDX are included in the ESG ranking. This study aims to examine how the role of the board of directors in the acquisition of ESG scores and its impact on company performance. To test the overall hypothesis, this study uses Path Analysis using Smart-PLS. This study found that board size has no effect on ESG, but board intensity can have a significant effect on ESG. ESG practices have no significant effect on financial performance. The size and intensity of board meetings have a significant effect on company performance, but ESG cannot mediate the effect of board size and intensity of board meetings on company performance partially.